Core structures and planar faults associated with <111> screw superdislocations in B2 alloys. (July 2019) - Yan, J.X.; Zhang, Z.J.; Li, K.Q.; Xia, Z.Y.; Yang, J.B.; Zhang, Z.F.
Abstract: The core structures, planar faults, and mobility associated with [111] screw superdislocations are systematically investigated by atomistic simulations using six different EAM potentials in FeAl. The results demonstrate that the core structures of [111] screw superdislocations transfer from two-fold into triple configurations, and the planar faults vary from metastable to unstable states in different FeAl alloys. The energy minimization (EM) approach is provided to quantitatively predict the core structures and planar faults of [111] superdislocations, where the Burgers vectors of partials and the state of planar faults are adjustable to optimize the system energy. Moreover, the consecutive transformation of core structures takes place before the activation of cross-slip under shear stresses at finite temperatures. In this case, the cross-slip mechanism dominated by core transformations is proposed, and it implies that the EM approach could be utilized to evaluate the cross-slip behaviors of superdislocations. Graphical abstract: Image 1 Highlights: The core structure and planar faults of screw [111] superdislocation are studied by atomic simulation in FeAl. The model is provided to determine the core structure and dislocation mobility in B2 alloys. The molecular dynamic simulations reveal the cross-slip behavior of screw [111] superdislocations. The planar faults vary from triple to two-fold states under external shear stresses. The core transformation is found to dominate cross-slip activations of [111] superdislocation.